Campus values : some considerations for collegians - Havice, Charles W. (New York : Scribner, 1968)
This small volume treats some of the most important topics in the world. They have to do with what it means to be a human in a period of mankind's history when the inquiry is unusually complex and difficult. Education has been the social institution through which the answers to our central quest for insight into ourselves and the universe traditionally have been given.
Aims of college education -- The campus and the generation gap -- Adventuring in social maturity -- Portrait of the freshman as a sexual being -- Drink and drugs on the campus -- Confronting college cheating -- Plagiarism : the gray area -- Extracurricular activities -- Extracurricular activities : part One : the invisible curriculum ; Part two : Fraternities, to join or not to join -- Responsible individual expression -- Creative criticism and campus protest -- Religion on campus -- Appendix: Responsibility and cooperative education -- Today's student and the college psychiatrist.
Includes bibliographical references.
Keywords: EDUCATION